2018
DOI: 10.1111/imj.13741
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal paracentesis: use of a standardised procedure checklist and equipment kit improves procedural quality and reduces complications

Abstract: The PC and EK improved rates of informed consent, appropriate documentation and protocol adherence. Significantly fewer procedure-related complications occurred after introduction of these tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Trained physicians must optimize pre- and post-procedural paracentesis safety checklists to develop system-wide protocols to help minimize any procedural complications. In fact, studies have shown that physicians utilizing a standardized procedure checklist and equipment kit demonstrated noted improvements in documentation rates, and most importantly, a significant decline in post-paracentesis complications [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trained physicians must optimize pre- and post-procedural paracentesis safety checklists to develop system-wide protocols to help minimize any procedural complications. In fact, studies have shown that physicians utilizing a standardized procedure checklist and equipment kit demonstrated noted improvements in documentation rates, and most importantly, a significant decline in post-paracentesis complications [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Local procedure protocol has been shown to improve rates of informed consent, appropriate documentation, and protocol adherence. Moreover, significantly lower procedure-related complications have been reported after the introduction of these protocols [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paracentesis is best performed by a doctor who is trained for the procedure. 31 Recently introduced co-axial insertion technique is better than the routine z-technique of inserting cannula for Large Volume Paracentesis (LVP). 32 LVP is removal of an amount greater than 5L of ascitic fluid and is performed when tense ascites leads to discomfort and respiratory embarrassment or in cases with refractory ascites.…”
Section: Diuretics and Salt Restrictionmentioning
confidence: 99%
“…32 LVP is removal of an amount greater than 5L of ascitic fluid and is performed when tense ascites leads to discomfort and respiratory embarrassment or in cases with refractory ascites. 31 Thrombocytopenia and coagulopathy do not preclude paracentesis FFP transfusion is not needed for correction of deranged INR prior to paracentesis for countering deranged INR. 33 Colloid Replacement: LVP ought to be followed by intravenous human albumin infusion to decrease the chances of PPCD.…”
Section: Management Of Large Volume or Tense Ascites Treatment Options Available Arementioning
confidence: 99%